Interview with Dr. José Antonio Fernández Molina - Lindo Fuentes, Héctor; Zúñiga Arias, Ana Yolanda (Revista de historia., 2019)
Interview with Dr. José Antonio Fernández Molina, with the objective to expose the historiographic development in Central America, in the voice of one of its maximum representatives and diligent critics. Also, it’s of the utmost interest knowing how this historian got started and the different processes which his formation faced, and the exercise of his academic craft. Participating in this interview are Dr. Héctor Lindo Fuentes and MSc. Ana Yolanda Zúñiga Arias.